2012
DOI: 10.1111/j.1442-200x.2012.03714.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between bronchopulmonary dysplasia and MBL2 and IL1‐RN polymorphisms

Abstract: MBL and IL 1 RN polymorphisms are closely related to low birthweight and increase the risk of neonatal sepsis and BPD development in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The IL-1 family of proinflammatory cytokines, particularly an imbalance of IL-1 and IL-1 receptor antagonist (IL-1RA) protein, has previously been implicated in BPD pathogenesis (20). IL-1RN polymorphisms have been associated with increased risk of BPD (7). IL-1RA and IL-1␤ proteins have been shown to be increased at DOL 1-3 in tracheal aspirate supernatants from patients who will develop BPD (7).…”
Section: L53mentioning
confidence: 99%
See 1 more Smart Citation
“…The IL-1 family of proinflammatory cytokines, particularly an imbalance of IL-1 and IL-1 receptor antagonist (IL-1RA) protein, has previously been implicated in BPD pathogenesis (20). IL-1RN polymorphisms have been associated with increased risk of BPD (7). IL-1RA and IL-1␤ proteins have been shown to be increased at DOL 1-3 in tracheal aspirate supernatants from patients who will develop BPD (7).…”
Section: L53mentioning
confidence: 99%
“…IL-1RN polymorphisms have been associated with increased risk of BPD (7). IL-1RA and IL-1␤ proteins have been shown to be increased at DOL 1-3 in tracheal aspirate supernatants from patients who will develop BPD (7). Activated alveolar macrophages have been shown to be a source of IL-1RA (18), and while we cannot sample the alveolar space, we hypothesize that DP and SP tracheal monocytes resemble other pulmonary monocytes/ macrophages as an important source of IL-1RA.…”
Section: L53mentioning
confidence: 99%
“…explored the connection between BPD and IL-1RN polymorphisms. Their research showed that IL-1RN 2/2 genotype increases the risk of BPD and of IL-1RN 1/1 genotype has protective character [ 23 ]. In our research we did not prove any influence of this polymorphism on BPD risk.…”
Section: Discussionmentioning
confidence: 99%
“… 15 BPD was classified into three groups in terms of BPD severity depending on the duration and level of supplemental oxygen and mechanical ventilatory support at 36 weeks postmenstrual age. 16 ROP was classified according to the International Classification of Retinopathy of Prematurity. 17 …”
Section: Methodsmentioning
confidence: 99%